Previous Moraxella catarrhalis Infection as a Risk Factor of COPD Exacerbations Leading to Hospitalization - Kyoko Yagyu; Takahiro Ueda; Atsushi Miyamoto; Riki Uenishi; Haruhiko Matsushita (COPD)
Haemophilus influenzae (H. influenzae) and Moraxella catarrhalis (M. catarrhalis) are associated with acute exacerbation of chronic obstructive pulmonary disease (AECOPD); however, their role in the pathogenesis of COPD is unknown. We retrospectively analysed the clinical data of patients with AECOPD (modified British Medical Research Council scale score, Global Initiative for Chronic Obstructive Lung Disease [GOLD] classification, pre-admission antibiotic and inhalant usage, sputum culture and epidemic influenza virus antigen test) for association with admission frequency. Among 169 eligible patients, pathogens were and were not detected in 64 and 105, respectively. The GOLD classification grade was higher in the non-detection group with a prior antimicrobial administration rate of 21.9% than in the detection group. H. influenzae and M. catarrhalis, each identified in 24.6% of the total number of detected pathogens, were the most common infectious bacteria. The GOLD classification grade was higher in the re-hospitalisation group than in the one-time hospitalisation group (p < 0.01). Regarding type of pathogen, M. catarrhalis infection (n = 16) was more common in the re-hospitalisation group. History of M. catarrhalis, H. influenzae infection and GOLD grade ≥ III were risk factors for re-hospitalisation, with odds ratios of 92.7 (95% confidence interval [CI]: 3.68–2340.0, p < 0.01), 20.1 (CI: 1.48–274.0, p < 0.05) and 9.83 (CI: 2.33–41.4, p < 0.01), respectively. These bacterial infections and severe airway limitation were associated with increased AECOPD frequency. Routine microbial monitoring may be useful for AECOPD prevention, reducing medical burden and improving prognosis.